Rare conditions mimicking bladder endometriosis (Indian Journal of Case Reports, 2018)
Benign conditions of the bladder such as cystitis cystica and Xanthogranulomatous cystitis (XC) are chronic inflammatory lesions which are usually rare in incidence. Here, we report 2 case reports wherein both the patients were diagnosed as bladder endometriosis for which segmental resection and partial cystectomy were done by the minimally invasive approach. Post-operative pathological examination revealed the lesions as cystitis cystica in one case and XC in another. To the best of our knowledge, this case of cystitis cystica mimicking as the bladder endometriosis is the 2nd case reported in the literature and case of XC forming a tumorous lesion is the 29th to be reported in the world literature.